Assessment of three Tropical Chlorophytes as Bioassay Organisms for Nitrogen and Phosphorus Enrichment in Freshwater Ecosystems - W.L, Chu; M.S, Ramadhona; S.M, Phang (Malaysian Journal of Science, 2007)
Enrichment of nitrogen and phosphorus in aquatic ecosystems can lead to excessive blooming of algae, resulting in eutrophication. The main objective of the present study was to assess the potential use of three tropical chlorophytes, namely Chlorella vulgaris UMACC 001, Scenedesmus quadricauda UMACC 041 and Ankistrodesmus convolutus UMACC 101 as test organisms for the bioassay of nitrogen and phosphorus. The minimal medium used in this study was 1% Bold's Basal Medium (BBM), which contained 0.03 mM NaNO₃ or NH₄Cl and 0.02 mM phosphate (KH₂PO₄ and K₂HPO₄). The algae were grown in the minimal medium added with NaNO₃ or NH₄Cl ranging from 0.03, 0.15, 0.75, 3.75 to 18.75 mM for 96 hours using flask cultures. The dilution water without nitrogen and phosphorus was used as the control. For the phosphate experiments, the cultures were grown at 0, 0.02, 0.10, 0.50, 2.50 and 12.50 mM phosphate (KH₂PO₄ and K₂HPO₄) in 1% BBM containing 0.03 mM NaNO₃ or NH₄Cl. There was no marked difference in the specific growth rates (µ) of the three chlorophytes in response to nitrogen and phosphorus enrichment. The percentage growth enhancement (PGE₉₆) based on the percentage increase of cell number at 96 hours compared to that attained in dilution water was a useful parameter for the bioassay of nitrogen and phosphorus. The suitability of the algae as test organisms was assessed based on the linearity of the relationship between PGE₉₆ and nitrogen and phosphorus concentration, as indicated by the regression coefficient (R²). It was also based on the EC₅₀, which was the effective concentration that gave a PGE₉₆ of 50%. Based on the two parameters, Chlorella vulgaris was found to be a suitable test organism for the bioassay of NaNO₃ (EC₅₀ = 0.56 mM; R² = 0.98) while Ankistrodesmus convolutus was suitable for the bioassay of NH₄Cl (EC₅₀ = 0.005; r²= 0.86). When grown on NaNO₃, the sensitivity of Chlorella vulgaris to phosphate enrichment was very low (EC₅₀ = 822.72 mM). In comparison, when grown on NH₄Cl, the three algae were sensitive to phosphate enrichment (EC₅₀ = 0.08 - 0.12 mM). The three algae would be useful for the bioassay of phosphate in water samples containing NH₄Cl as the dominant nitrogen source.